TreatPlan: Web-Based System Development for Clinic Check-Up Reservation - Mokhsin@Misron, Mudiana; Mohamad Ramli, Nurul Afiqah; Abd Munir, Azri Bima; Syed Nulzurin, Syarifah Nurin Hasya; Shahruddin, Nur ‘Ain Sofea (Multidisciplinary Applied Research and Innovation, 2022)
The current issue that many people have with getting a medical checkup at a specific clinic or hospital is that it takes a longer waiting time. Aside from that, the doctor will have no idea what the patient’s schedule is. Certain locations tend to increase the facility’s crowdedness to some extent. After taking the approach of observing clinics and healthcare institutes, it is overcrowded with patients and some of the patients are not even sure of their appointments, but they come either way. The medical staff are swamped with phone calls from patients asking for their treatment appointment schedule. TreatPlan is a system created to help a community where they need a treatment to be planned beforehand. The system’s ambition is to fend off time consuming waiting duration that is especially hard for older people. The system also wants to help patients that are unsure of their own scheduled treatment or what might come up with their plan. Because of the systematic scheduled treatment, this will help the facility not to be overcrowded. The system has a user-friendly interface because of the straightforward menus and is not built for every clinic due to different business rules and that is what makes the system exclusive. The system helps to give people convenience and flexibility to plan their medical checkup comfortably according to their schedule. On the other hand, the doctors also gain the benefits that they can also manage their schedule to sync with their patients.